(untitled) (Research, Society and Development, 2022)
The present study aims to analyze the scientific production on premature birth and air pollution, using the Fuzzy approach. A search was carried out from articles in the SCOPUS database, with the keywords “premature birth” or “preterm birth”, “air pollution” and “fuzzy” during the period from 2000 to 2020. Soon after this step, for the analysis of scientific mapping of future trends, the SciMAT software was used, followed by the use of the VOSviewer software for the construction of maps of co-occurrences. Three combinations were performed for analysis, air pollution linked to fuzzy logic, and premature or preterm birth associated with the two factors separately. The combinations resulted in 743 unduplicated articles found in 76 countries, with 381 authors published in 255 different journals. No articles were identified that associated prematurity, air pollution and fuzzy approach together, making this a gap in the literature and a great research opportunity. The study of this topic is of great relevance to society, as it can assist in the creation of public policies, reduction of health-related expenses and increase in the quality of life of pregnant women and newborns throughout their lives.